CHALLENGES OF IMPLEMENTING THE UNDERGROUND GAS STORAGE PROJECT IN GEORGIA - Lena Shatakishvili; Tamar Shoshiashvili (World Science, 2023)
The launch of the Southern European Gas Corridor, the real prospect of increasing gas transit volumes for Georgia, has made even more critical the need to build an underground gas storage facility in Georgia. The technical and economic evaluation of gas storage in different prospective locations has already been done, there is also a gas storage project. The prospects for the construction of a gas storage facility in Georgia, and the need for the existence of a gas storage facility as an important tool for the country's energy security are discussed in the article.